Zooplankton fecal pellet flux in the abyssal northeast Pacific: A 15 year time‐series study. (3rd May 2013) - Wilson, S. E.; Ruhl, H. A.; Smith, Jr., K. L.
Abstract : Sinking particulate material collected in sequencing sediment traps moored at 3500 m depth (600 m above bottom) from 1993 to 2008 at the abyssal time‐series Sta. M in the northeast Pacific was analyzed via microscopy and digital imaging. Intact zooplankton fecal pellets were quantified and size, shape, and carbon content were measured. The most common identifiable fecal pellets were from larvaceans, which feed on small particles. Other abundant fecal pellets were likely produced by large copepods and euphausiids. The proportion of identifiable fecal pellet carbon to total particulate organic carbon (POC) flux varied and ranged from 3.3% to 47.7%. Fecal pellet flux and fecal pellet‐derived carbon flux was lowest in February, and highest in May, August, and November samples. The proportion of total POC in identifiable fecal pellets was negatively correlated to overall POC flux and to indicators of climate variability. The North Pacific Gyre Oscillation and Northern Oscillation Index climate indices were negatively correlated to the dominance of fecal pellets in POC flux, with changes in fecal pellet fluxes temporally lagging climate‐related changes by about 3 and 5 months, respectively. Variations in zooplankton distribution and abundance affect biogeochemical cycling to abyssal depths, further demonstrating how a changing climate may affect deep‐sea ecology. The dominance of zooplankton fecal pellets can shift proportionally, providing new insight into the processes controlling marine carbon sequestration in the deep sea.